Effects of Hydroxycitric Acid Supplementation on Body Composition, Obesity Indices, Appetite, Leptin, and Adiponectin of Women with NAFLD on a Calorie-Restricted Diet - Helda Tutunchi; Sara Arefhosseini; Solmaz Nomi-Golzar; Mehrangiz Ebrahimi-Mameghani (International Journal of Clinical Practice)
Background. This trial assessed the effects of a calorie-restricted diet (CRD) with hydroxycitric acid (HCA) supplementation on appetite-regulating hormones, obesity indices, body composition, and appetite in women with nonalcoholic fatty liver disease (NAFLD). Methods. This study was carried out on 44 overweight/obese women with NAFLD. The patients were randomly assigned into two groups, namely, “Intervention group” (receiving individual CRD plus HCA tablets per day) and “Control group” (receiving only CRD) for eight weeks. Obesity indices, body composition, appetite status, and serum levels of leptin and adiponectin were assessed before and after the intervention. Results. Forty patients completed the trial. At the end of the trial, although significant reductions were found in most of the studied obesity indices in the intervention group, there was only a significant decrease in waist circumference and waist-to-height ratio in the control group. Fat mass and muscle mass significantly decreased in the intervention group (p=0.044 and p=0.024, respectively), and the reduction in visceral fat in the intervention group was significantly greater than that in the control group (−0.49 kg vs −0.37 kg, p=0.024). Intra- and intergroup differences in serum leptin and adiponectin levels and their ratios before and after the trial were not significant. We found a negative and marginally significant correlation between percent of changes in serum adiponectin level and percent of changes in visceral adipose tissue (VAT) (r = −0.429, p=0.067) and BMI (r = −0.440, p=0.059) as well as an inverse relationship between percent of changes in leptin/adiponectin with VAT (r = −0.724, p<0.001) in the intervention group. Conclusion. HCA plus weight loss diet could significantly reduce visceral adipose tissue without any significant changes in serum leptin and adiponectin levels.